The Relationship of Different Dimensions of Social Support with Older Adults' Quality Of Life in the 8th District of Tehran in 2013 - Shahnaz Rimaz; Hasan Gharibnavaz; Jamileh Abolghasemi; Shirin Seraji (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Older adults' quality of life and factors affecting it such as social support are a major concern because they are among vulnerable groups and should receive different supports to ensure their quality of life. This study aimed to determine the relationship between social support and quality of life in the older adults living in the 8th district of Tehran. Materials and Methods: This cross-sectional study was conducted on 240 older adults living in the 8th district of Tehran. Participants were selected via cluster sampling method. We used LEIPAD quality of life questionnaire to measure the quality of life and Norbeck Social Support Questionnaire to evaluate social support. Data were analyzed in SPSS-20 using Mann-Whitney test, Kruskal-Wallis test and Spearman's correlation. Results: The mean score of quality life was 68.9 of 93 in men and 97.6 of 93 in women and this difference was not statistically significant (P=0.404). Education level had a significant effect on both quality of life and social support (P<0.05). Furthermore, there was a significant relationship between social support and some dimensions of the quality of life, e.g. physical, social and cognitive function (P<0.05). Conclusion: Different dimensions of social support were higher in men than in women. Although the relationship between dimensions of social support on the overall quality of life score was not statistically significant, the significant relationship between dimensions of social support and dimensions of quality of life show that social support can impact quality of life.